BEYOND THE WALLS: Representing Penginyongan Cultural Heritage in Islamic Academic Libraries - Feby Lestari Supriyono; Eni Nur Aeni; Juairiah Juairiah; Siti Wahdah; Wahyu Triani (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
This article examines the role of Islamic academic libraries in representing and reconstructing local cultural heritage, with particular reference to Penginyongan culture in Banyumas, Central Java. Amid the pressures of globalization and cultural homogenization, the preservation of local identity increasingly intersects with Islamic institutional frameworks. This study aims to analyze how cultural representation is produced, negotiated, and legitimized within an Islamic epistemic context. Employing a qualitative interpretive case study at the UIN SAIZU Library, data were collected through in-depth interviews, participant observation, and document analysis. The analysis draws on Stuart Hall’s theory of representation and Pierre Bourdieu’s concept of cultural capital, contextualized within Islamic principles of knowledge preservation (hifzh at-turâts) and public benefit (mashlahah). The findings reveal three key dynamics: first, library collections serve as institutional mechanisms that legitimize Penginyongan culture within academic and religious discourse; second, curatorial and spatial practices reflect a dialogical integration of Islamic values and local wisdom; and third, these practices facilitate the reconstruction of cultural identity across diverse audiences. This study argues that Islamic academic libraries function as cultural intermediaries that actively shape meaning, strengthen cultural resilience, and redistribute cultural capital among marginalized communities.